2022
DOI: 10.21873/invivo.12903
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Glasgow Prognostic Score and Prognostic Nutritional Index as Prognostic Markers in Patients With Metastatic Breast Cancer Treated With Eribulin

Abstract: Aim: To examine the role of the Modified Glasgow Prognostic Score (mGPS) and Prognostic Nutritional Index (PNI) as prognostic markers for patients with metastatic breast cancer (MBC). Patients and Methods: We investigated the associations of clinico-pathological factors with time-totreatment failure (TTF) and overall survival (OS) in 110 patients with MBC treated with eribulin. Results: C-Reactive protein >1 mg/dl, albumin <3.5 g/dl, mGPS=2, and PNI <40 were significant predictors of shorter TTF in univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Of 43 records screened for full-text eligibility, 27 studies were excluded based on the following reasons: nine articles were not using breast cancer specific population, nine articles lacked data pertaining to the outcomes, five articles lacked data pertaining to the variable of interest, and four articles were omitted as they were review articles. Ultimately, the remaining 16 articles [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] with a total of 7457 breast cancer patients were included in the final analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of 43 records screened for full-text eligibility, 27 studies were excluded based on the following reasons: nine articles were not using breast cancer specific population, nine articles lacked data pertaining to the outcomes, five articles lacked data pertaining to the variable of interest, and four articles were omitted as they were review articles. Ultimately, the remaining 16 articles [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ] with a total of 7457 breast cancer patients were included in the final analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In metastatic breast cancer patients treated with eribulin, comparing mGPS and PNI, low PNI and positive mGPS were shown to be related to TTF in univariate analysis. Low PNI was proven to have an effect on OS and TTF in multivariate analysis [ 35 ]. In contrast to our study, this study comprised metastatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Forrest et al (25) first reported the prognostic value of the GPS in patients with advanced non-small-cell lung cancer in 2003. Subsequently, in a patient with MBC, the GPS was reported to be a predictor of cancer-specific survival (12), or progression-free survival or the response rate (26,27).…”
Section: Discussionmentioning
confidence: 99%